Uji Daya Hambat Antibakteri Ekstrak Air, Etanol, Dan Kloroform Daun Teh Hijau (Camellia Sinensis L. Kuntze) Terhadap Pertumbuhan Bakteri Escherichia Coli - Ghaliyah Hidastri Rukmana; Ahwan; Fadilah Qonita (An-Najat, 2024)
Infection is a major disease problem in the world, especially in Indonesia. One of the bacteria that causes infection is Escherichia coli. A common symptom of infection is diarrhea, infection can be treated using antibiotics. Antibacterial compounds derived from plant extracts are green tea leaves (Camellia Sinensis L. Kuntze). This study aims to determine the differences in the inhibitory power tests of water, ethanol and chloroform extracts of green tea leaves (Camellia Sinensis L. Kuntze) against bacterial growth Escherichia coli. In antibacterial testing, the disc diffusion method is used, and the data is processed using the test Oneway ANOVA. The test results showed that all samples had antibacterial activity. The strong inhibitory category is owned by ethanol extract of green tea leaves with a concentration of 16% (13.23 ± 0.10) mm and 64% (18.35 ± 0.05) mm, chloroform 16% (11.38 ± 0.19 ) mm and 64%, (13.48 ± 0.24) mm, water 64% (12.25 ± 0.05) mm. The moderate inhibitory power category belongs to water extract concentrations of 4% (7.87 ± 0.08) and 16% (8.45 ± 0.22) mm. Meanwhile, the positive control of 3% chloramphenicol has a very strong inhibitory power with an average zone of inhibition of (29.38 ± 0.15) mm, and the weak inhibitory power of the negative control of 1% DMSO is (0 ± 0.00) mm. . Based on the research results, it can be concluded that the three extracts of water, ethanol and chloroform were proven to have antibacterial activity against Escherichia coli which is significantly different (p value) < 0,05.